Influence of Varying Dentin and Enamel Layer Thicknesses of Nano-composite Resins on Color Match between Lithium Disilicate Dental Ceramic and Composite Resins - Elmira Saati Khosroshahi; Elmira Jafari Navimipour; Fatemeh Pournaghi Azar; Mehdi Abed-Kahnamoui; Mahmoud Bahari (Tehran University of Medical Sciences, 2021)
Objectives: The aim of this study was to evaluate the influence of varying dentin and enamel layer thicknesses of two nano-composite resins on color match of composite resins and lithium disilicate dental ceramic. Materials and Methods: Twenty-six specimens of two types of nano-composite resins, Opallis and Vittra, were fabricated using the two-layered technique with different thickness ratios of enamel and dentin composites (A2 shade) with a total thickness of 1.2mm. Thirteen discs of the same shade and thickness of IPS e.max Press LT (low translucency) lithium disilicate dental ceramic were also fabricated. Specimen color was measured with a spectrophotometer. The difference in color (ΔE00) of composite and ceramic specimens, and the translucency parameter (TP) of all specimens were calculated. Data were analyzed using multi-factor ANOVA (P<0.05). Results: The color difference (ΔE00) values of composites and ceramic were not clinically acceptable in any areas of either of the two composites (ΔE00>2.25). But ΔE00 between the two composite resins was in the clinically acceptable range (ΔE00<2.25). The mean TP value of IPS e.max Press was greater than that of Vittra and lower than that of Opallis. Conclusion: In similar thicknesses, composite resins with any enamel/dentin thickness ratio could not successfully simulate the color and translucency of IPS e.max Press LT ceramic.